Influence of Gamma Radiation on Optical and Dielectric Properties of Dyed Polyvinyl Alcohol Film Dosimeters - Lepit, Ajis (2004)
The influence of y-rays on the optical absorption and inelastic scattering, dielectric properties and conductivity of radiation-sensitive dyed polyvinyl alcohol (TBIPVA) film dosimeters containing chloral hydrate and acid-sensitive Thymol blue dye were evaluated for possible use as food irradiation indicators. The dyed PVA films of different concentrations of chloral hydrate were irradiated with the absorbed doses ranging up to 12 kGy using y-rays from Cobalt-60. The dehydrochlorination of chloral hydrate and radiolysis of water molecules induced by ionising radiations accelerated the formation of hydrochloric acid in the polymer matrix, which caused the change in colour of the dosimeters from yellow to red at the critical doses depending on the concentration of chloral hydrate. This radiation-induced colour change was analysed using UV-Vis spectrometer, where the absorption spectra produced two visible maximal bands, peaking at 445 nm and 554 nm. The dose response at 445 nm and 554 nm increases and decreases respectively with absorbed dose. The inelastic Raman scattering spectra of photons corresponding to the Raman frequency shifts of unirradiated and irradiated films were measured using a dispersive Raman spectrometer, which provide direct evidence of molecular structure changes induced by ionising radiation and the subsequent chemical effects. The spectral intensities of Raman shifts at 815, 1984, 2350 and 2560 cm-' bands correspond to C-CI, C=O, C=C and S-H bonds respectively were studied, which provide the dose response to the molecular vibration of the dosimeters. From dielectric and conductivity studies it is found that the dyed polymer dosimeters are ionic polymer materials. The dielectric constant (E'), dielectric loss (E") and the electrical conductivity o(o) characteristics of the dosimeters were measured at different frequencies ranging from 20 Hz to I MHz. The dielectric constant and dielectric loss increase with absorbed dose at low frequencies and are independent of dose at higher frequencies for all chloral hydrate concentration. The AC conductivity (o) increases with absorbed dose and frequency due to the formation of radiationinduced free radicals, cations and anions in the polymer matrix and due to ejected electrons in the conduction bands. Thus, the resistance derived from the impedance measurement, decreases with absorbed dose. Finally, the films were subjected to stability tests using digital densitometry method at different time intervals during post-irradiation storage. The results show the change in optical density is minimal over the period of 70 days for all irradiated samples. This suggests the dosimeters have optical absorption stability characteristics for use as alternative radiationsensitive dosimeters in irradiation facilities as long as they are shielded from sunlight or fluorescent lighting by wrapping with black plastic bag.